PROFILE OF STUDENT ALGEBRA THINKING ABILITY BASED ON MATHEMATICAL PRELIMINARY SKILLS - Wilujeng, Hestu (International Journal of Research -GRANTHAALAYAH, 2017)
This study aims to explore and analyze the students' algebraic thinking skills that have early mathematical abilities. This research is an explorative research with qualitative approach. The Subject consists of 3 students who have high early, medium and low mathematical ability. The research instrument is self-researcher with supporting instrument that is about the algebra thinking ability test and interview guidance. The ability to think algebra includes problem-solving skills, mathematical modeling and generalization. Data analysis used qualitative descriptive analysis with guidance indicators of algebraic thinking ability while data analysis of interview uses data reduction step, data presentation, and decision making. Testing data validity using method triangulation. The result of the research is that students with high mathematical preliminary skills (MPS) can solve the problem well, MPS students are able to understand and plan the settlement well, but the mathematical modeling is not accurate so result in the settlement whereas the low MPS students in understanding the problem just read but do not have the solution plan.